Templated‐Construction of Hollow MoS2 Architectures with Improved Photoresponses - Chao Gao; Yingdong Han; Kun Zhang; Tian Wei; Zhang Jiang; Yang Wei; Lisha Yin; Fabio Piccinelli; Cheng Yao; Xiaoji Xie; Marco Bettinelli; Ling Huang (Advanced Science, 2020)
Abstract Despite the outstanding optoelectronic properties of MoS2 and its analogues, synthesis of such materials with desired features including fewer layers, arbitrary hollow structures, and particularly specifically customized morphologies, via inorganic reactions has always been challenging. Herein, using predesigned lanthanide‐doped upconversion luminescent materials (e.g., NaYF4:Ln) as templates, arbitrary MoS2 hollow structures with precisely defined morphologies, widely variable dimensions, and very small shell thickness (≈2.5 nm) are readily constructed. Most importantly, integration of the near‐infrared‐responsive template significantly improves the photoresponse of up to 600 fold in device made of NaYF4:Yb/Er@MoS2 compared with that of MoS2 nanosheets under 980 nm laser illumination. Multichannel optoelectronic device is further fabricated by simply changing luminescent ions in the template, e.g., NaYF4:Er@MoS2, operating at 1532 nm light excitation with a 276‐fold photoresponse enhancement. The simple chemistry, easy operation, high reliability, variable morphologies, and wide universality represent the most important advantages of this novel strategy that has not been accessed before.